Effects of a disordered urbanization: “the cities with their backs to the river” in the Cuiabá River Valley Metropolitan Region - RMVRC/MT - Zili Salmoria, Fabiana; Rombi de Godoy, Jeane Aparecida (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The growing and disorderly Brazilian urbanization caused a series of impacts on the environment, among them the rivers pollution and the irregular banks occupations, being a characteristic phenomenon of the Cuiabá River Valley Metropolitan Region, where “the cities turned their backs to the river” developing without considering the different potentials of the existing watercourses in its territory. With this approach, this article aimed to understand this dynamic, considering that this river is responsible for the water supply of both cities, and a Pantanal Mato-Grossense affluent, making it important to identify the contradictory relationships between socio-environmental issues and the application and urban legislation supervision, by mapping PPAs, carried out in order to verify the degradation of the Cuiabá River and urban water streams in the Cuiabá-Várzea Grande conurbation. The applied methodology, based on bibliographical, documentary, and empirical research, involved studies about the theme and the region history, analyzes the legislation, maps, satellite images, thematic maps preparation from the studied areas (multiple cases) and on-site visits generating photographic records for analysis the socio-environmental impacts arising from irregular occupations verified in the protection strips (PPAs). The results demonstrated the importance of continuing new research, as well as being able to subsidize decision-making processes, formulation of urban and environmental legislation, public policies aimed at socio-environmental protection of remaining areas, which are relevant for improving the quality of life and the region environment.